The Influence of Social Media Marketing and Viral Marketing on BrandLoyalty and Purchase Intention among Generation Z in the Digital Era(A Study on Daviena Product Users in TikTok Shop E-Commerce) - ervina; M. Sulhan (Journal of Economic, Management and Entrepreneurship, 2025)
Ervina, a student of the Business Administration Study Program at Yudharta University Pasuruan,conducted a study in July 2025 entitled "The Influence of Social Media Marketing and Viral Marketingon Brand Loyalty and Purchase Intention Among Generation Z in the Digital Era: A Study on Usersof Daviena Products on TikTok Shop E-Commerce."This study aims to analyze the influence of SocialMedia Marketing and Viral Marketing on Brand Loyalty and Purchase Intention among Generation Zusers of Daviena products on the TikTok Shop e-commerce platform. A quantitative research methodwas employed, with data collected through questionnaires distributed to 150 Generation Z respondentsin Pasuruan Regency. Data analysis was conducted using the Structural Equation Modeling (SEM)approach based on Partial Least Squares (PLS).The findings reveal that Social Media Marketing has asignificant positive effect on both Brand Loyalty and Purchase Intention. In contrast, Viral Marketingdoes not exhibit a significant influence on either Brand Loyalty or Purchase Intention. Additionally,Brand Loyalty is not found to have a significant impact on Purchase Intention. The R-Square values are11.7% for Brand Loyalty and 4.8% for Purchase Intention, indicating that a considerable portion ofvariance is explained by variables outside the scope of this study.These findings imply that businesspractitioners, particularly local brands in the digital era, should optimize their marketing strategiesthrough TikTok to foster customer loyalty and enhance the purchase intention of young consumers.The study also recommends further evaluation of viral marketing strategies and emphasizes theimportance of considering other influential factors that drive Gen Z’s purchasing decisions on digitalplatform